Risk factor analysis and preventive health behavior in the control of blood glucose among patients with type II diabetes mellitus: A community-based cross-sectional study - Panjaitan, Panondang N.; Weraman, Pius; Adu, Apris A. (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Diabetes Mellitus (DM) Disease is rapidly increasing in Indonesia. This disease is defined as either our random blood glucose level >200 mg/dL or fasting blood glucose level >126 mg/dL. Maintaining a controllable blood glucose level (either less than 200 mg/dL for random blood glucose level or less than 126 mg/dL for fasting blood glucose level) in Type II DM patients is obviously playing an important role to avoid any complications such as stroke disease, heart disease and kidney failure. The purpose of this research is to analyze the risk factors contributing to uncontrolled blood glucose in Type II DM patients who come to visit Alak Public Health Centre, city of Kupang. Methods: This research is a quantitative analytic study with cross sectional method, with a total sample of 68 respondents. The statistical analysis carried out by Computer Program is univariate, bivariate and multivariate analysis. Findings: The result of this research shows significant factors contributing to uncontrolled blood glucose level are Body Mass Index (BMI) p value=0.003, patients compliance (p value=0.003), Knowledge of DM (p value=0.011), Regular Physical Activity (p value=0.000), Food Order (p value=0.024), Smoking (p value=0.524) and family support (p value=0.077). The dominant factor which has more significant effect on uncontrolled blood glucose level in Type II DM patients is regular physical activity (p value=0.001). Conclusion: Uncontrolled blood glucose in Type II DM patients is strongly influenced by multiple behavioral and lifestyle factors, with regular physical activity being the most dominant. Strengthening patient education, compliance, and health promotion at the primary care level is essential to improve glycemic control and prevent complications. Novelty/Originality of this article: In order to maintain controlled blood glucose level in Type II DM patients it is suggested that all health workers in public health centre pay more promotive measure to risk factors affecting the bllood glucose in Type II DM patients with effective medias and methods.